2016
DOI: 10.1016/j.envint.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Overall and class-specific scores of pesticide residues from fruits and vegetables as a tool to rank intake of pesticide residues in United States: A validation study

Abstract: Pesticide residues in fruits and vegetables are among the primary sources of pesticide exposure through diet, but the lack of adequate measurements hinder the research on health effects of pesticide residues. Pesticide Residue Burden Score (PRBS) for estimating overall dietary pesticide intake, organochlorine pesticide score (OC-PRBS) and organophosphate pesticide score (OP-PRBS) for estimating organochlorine and organophosphate pesticides-specific intake, respectively, were derived using U.S. Department of Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…However, our previous work has shown that higher intake of high–pesticide residue FVs was significantly associated with higher levels of urinary pesticide metabolites, supporting the use of the PRBS as an adequate measure to characterize exposure to pesticides through diet. 26 Second, our methodology does not allow linking specific pesticides to adverse reproductive effects. Further confirmation studies, preferably accounting for common chemical mixtures used in agriculture by biomarkers, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous work has shown that higher intake of high–pesticide residue FVs was significantly associated with higher levels of urinary pesticide metabolites, supporting the use of the PRBS as an adequate measure to characterize exposure to pesticides through diet. 26 Second, our methodology does not allow linking specific pesticides to adverse reproductive effects. Further confirmation studies, preferably accounting for common chemical mixtures used in agriculture by biomarkers, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although most OP pesticides were withdrawn from residential use in the US in the early 2000s, data from the 2007–2008 National Health and Nutrition Examination Survey (NHANES) indicate that exposure remains common. 34,35 OP exposure pathways in the non-agricultural US population include OP pesticide residues on food, 36,37 environmental exposures to remaining residues from residential pesticide application, 38 and non-agricultural occupational exposures. 39 Assessments of OP pesticide exposure in non-agricultural US populations have focused on vulnerable communities, and have been largely limited to analyses of prenatal and early life OP exposure and child development.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are classified into insecticides, herbicides, fungicides and many other substances, while there are three main chemical groups of them which are carbamates, organophosphorous and organochlorinated pesticides (Hu et al, 2016). Pesticides are classified into insecticides, herbicides, fungicides and many other substances, while there are three main chemical groups of them which are carbamates, organophosphorous and organochlorinated pesticides (Hu et al, 2016).…”
Section: Pesticides and Risk Assessmentmentioning
confidence: 99%
“…Pesticides are defined as any substances or substance mixtures that are applied for preventing, destroying or repelling of pests. Pesticides are classified into insecticides, herbicides, fungicides and many other substances, while there are three main chemical groups of them which are carbamates, organophosphorous and organochlorinated pesticides (Hu et al, 2016). Pests and diseases may make up to one-third of loss of crop; therefore, it is very important for using pesticides to increase agricultural production (Sharma et al, 2010;Misra, 2015;Misra et al, 2016).…”
Section: Pesticides and Risk Assessmentmentioning
confidence: 99%